2015
DOI: 10.3390/ijms161023382
|View full text |Cite
|
Sign up to set email alerts
|

Combination of MiR-378 and MiR-210 Serum Levels Enables Sensitive Detection of Renal Cell Carcinoma

Abstract: Serum microRNAs are emerging as a clinically useful tool for early and non-invasive detection of various cancer types including renal cell carcinoma (RCC). Based on our previous results, we performed the study to analyze circulating serum miR-378 and miR-210 in patients with various histological subtypes of RCC. RNA was purified from blood serum samples of 195 RCC patients and 100 healthy controls. The levels of miR-378 and miR-210 in serum were determined absolutely using quantitative real-time PCR. Pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
80
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 16 publications
(18 reference statements)
4
80
3
Order By: Relevance
“…78 The use of more than one miRNA is generally recommended to obtain improved accuracy and robustness of results. 72 which is lower than the AUCs that had been reported in studies without independent study cohorts. 68,70,71 In two studies, a decline in the concentration of miR-210 and miR-378 was observed after nephrectomy for treatment of RCC 70,72 , and both miRNAs were suggested as potential indicators of cancer recurrence in follow-up monitoring of patients with RCC.…”
Section: [H1] Biofluid Mirnas In Kidney Cancercontrasting
confidence: 43%
See 4 more Smart Citations
“…78 The use of more than one miRNA is generally recommended to obtain improved accuracy and robustness of results. 72 which is lower than the AUCs that had been reported in studies without independent study cohorts. 68,70,71 In two studies, a decline in the concentration of miR-210 and miR-378 was observed after nephrectomy for treatment of RCC 70,72 , and both miRNAs were suggested as potential indicators of cancer recurrence in follow-up monitoring of patients with RCC.…”
Section: [H1] Biofluid Mirnas In Kidney Cancercontrasting
confidence: 43%
“…72 which is lower than the AUCs that had been reported in studies without independent study cohorts. 68,70,71 In two studies, a decline in the concentration of miR-210 and miR-378 was observed after nephrectomy for treatment of RCC 70,72 , and both miRNAs were suggested as potential indicators of cancer recurrence in follow-up monitoring of patients with RCC. Only one study demonstrated that miRNA expression could function as an independent prognostic marker, in which an increased expression level of miR-221 was associated with poor overall survival.…”
Section: [H1] Biofluid Mirnas In Kidney Cancercontrasting
confidence: 43%
See 3 more Smart Citations